Global Trends of Mean and Inequality in Multidimensional Wellbeing: Analysis of 1.2 Million Individuals From 162 Countries, 2009–2019 - Shiba, Koichiro; Cowden, Richard G.; Gonzalez, Natasha; Lee, Matthew T.; Lomas, Tim; Lai, Alden Yuanhong; VanderWeele, Tyler J. (Frontiers in Public Health, 2022)
Introduction: Human flourishing is a multidimensional concept characterized by a state of complete well-being. However, much of the prior research on well-being has principally focused on population averages assessed using a single item of well-being. This study examined trends in population averages and inequalities for a multidimensional index of well-being and compared emergent patterns with those found for Cantril’s ladder, a measure of life satisfaction commonly used as a unidimensional index of well-being. Methods: Data were from the Gallup World Poll from the years 2009-2019, a repeated cross-sectional survey of nationally representative samples comprising approximately 1.2 million individuals from 162 countries. We assessed five domains of flourishing: 1) happiness, 2) health, 3) purpose, 4) character, and 5) social relationships. We used the Gini Index to estimate inequalities in well-being within populations. We examined and compared country ranking, global and region-specific trajectories of mean and inequality, and relationships with age for flourishing and Cantril’s ladder. Results: Although all trends were highly correlated across the two metrics of well-being, we identified distinct patterns in flourishing concerning geography, time, and age relationships that were not observed for Cantril’s ladder. Temporal trends and age relationships were different across domains of flourishing. Evidence of changing inequalities in well-being was also found, even when population averages were high or stable over time. Conclusion: Comprehensive measures of well-being are needed to capture the complex and changing patterns of well-being both within and across populations.